2020
DOI: 10.1002/bit.27479
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization rapidly selects for chemoresistant ovarian cancer cells with enhanced ability to enter dormancy

Abstract: Around 20–30% of ovarian cancer patients exhibit chemoresistance, but there are currently no methods to predict whether a patient will respond to chemotherapy. Here, we discovered that chemoresistant ovarian cancer cells exhibit enhanced survival in a quiescent state upon experiencing the stress of physical confinement. When immobilized in stiff silica gels, most ovarian cancer cells die within days, but surviving cells exhibit hallmarks of single‐cell dormancy. Upon extraction from gels, the cells resume prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…A subsequent study we conducted with dormancy-capable ovarian cancer cell lines (SKOV-3 and OVCAR-3) further showed that the state of dormancy enhanced chemoresistance. 50 Studies conducted by others on MDA-MB-231 cells encapsulated in photo-crosslinked RGDS laden PEG gels support our findings that high matrix stiffness, independent of adhesion, is sufficient to induce single cell dormancy. 44 Using a collagen-PEG gel, Reynolds et al also confirm that immobilization in stiff gels inhibits proliferative activity of MDA-MB-231s even in the presence of strong ECM protein binding.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…A subsequent study we conducted with dormancy-capable ovarian cancer cell lines (SKOV-3 and OVCAR-3) further showed that the state of dormancy enhanced chemoresistance. 50 Studies conducted by others on MDA-MB-231 cells encapsulated in photo-crosslinked RGDS laden PEG gels support our findings that high matrix stiffness, independent of adhesion, is sufficient to induce single cell dormancy. 44 Using a collagen-PEG gel, Reynolds et al also confirm that immobilization in stiff gels inhibits proliferative activity of MDA-MB-231s even in the presence of strong ECM protein binding.…”
supporting
confidence: 88%
“…Note that serum starvation induces dormancy via p38 phosphorylation and ERK dephosphorylation, and therefore is considered a positive control 55. The p38:ERK activity ratio after 3 days of immobilization in MSPEG was 2.80 ± 0.57 times that of the TCPS control, a value similar to that measured in cells grown in serum-free media (3.02 ± 1.69) (Figure6a,b).We also used qRT-PCR to explore the expression changes in proliferation intermediate genes, which are indicative of dormancy in ovarian cancer cells 50. CDK-cyclin complexes such as cyclindependent kinase 2 (CDK2), cyclin D1 (CCND1), and cyclin E1…”
supporting
confidence: 66%
See 2 more Smart Citations
“…For instance, braintropic cells are known to overexpress ST6GALNAC5 [36] which is a sialyltransferase that transfers sialic acid to oligosaccharides that can alter both cell-cell and cell-ECM interactions. [70,71] ST6GALNAC5 mediates infiltration into the brain by enhancing adhesion to, and interactions with, brain endothelial cells allowing penetration through the blood brain barrier. [36] In the same manner that ST6GALNAC5 mediates cell-ECM interactions in the brain, ST6GALNAC5 may also alter ECM interactions in the hydrogels implemented here, leading to the observed existence as cell clusters rather than solitary cells observed in gel 2.…”
Section: Discussionmentioning
confidence: 99%